USING THE RELEVANT PERSON’S EXPERIENCE AND THE ARTIFICIAL INTELLIGENCE-DERIVED MATERIALS TO IMPROVE SPEAKING DURING DISCUSSIONS - EDY SUSENO (Innovare Journal of Social Sciences, 2025)
Oral communication of ideas appears to be challenging for English as a Foreign Language learners. 17 pupils participated in the speaking class to deal with this problem. They volunteered to participate in the teaching and learning process. The instructor prepared in order to begin. He developed a platform for idea sharing in the classroom. The WhatsApp group is the main focus. The artificial intelligence (AI)-sourced conversation content was displayed on the screen. The pupils acquired the ability to understand it. The instructor then asked the class to have a discussion about the material’s content. When expressing their viewpoints, the students include a few examples from their own experiences. After the discussion period, the instructor presented the feedback. A qualitative examination of the information obtained from the process of instruction and learning. It has been determined that enhancing the conversation themes by integrating the students’ pertinent experiences with the AI-derived resources helps them become more proficient speakers. These kinds of findings could be modified by the instructor to teach the pertinent subjects. It also encourages other researchers to make more thorough observations.